EVALUASI PERSIAPAN MENGAJAR GURU EKONOMI BERDASARKAN KURIKULUM 2013 DI SMA NEGERI SE-OGAN ILIR - Ali Barka; Yulia Djahir; Ikbal Barlian (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2015)
This study aims to Know Teachers’ teaching Preparation Teaching Economics in Implementing Curriculum 2013 at SMA Negeri in the district Ogan Ilir, correlating to the preparation in the form of an annual program, the semester program, Syllabus, RPP (Lesson Plan), media / props, LKS (Student Worksheet), Task Sheet, Sheets of research, and Textbook prepared by the Economics teachers in the district of Ogan Ilir on the basis of the 2013 curriculum. This study is a qualitative research, and the data collection techniques used here is In the form of interview techniques and documentation. Interview data is used to determine the ability of teachers to understand the preparations made in accordance with the 2013 curriculum. Interviews were conducted in three meetings on economics teachers at SMA in the district of Ogan Ilir and documentation of data is used to support the interview data. Overall, Data on the interview show that the result is